A lanthanide coordination polymer as a ratiometric fluorescent probe for rapid and visual sensing of phosphate based on the target-triggered competitive effect. Issue 37 (9th September 2020) - Han, Lei; Liu, Shi Gang; Yang, Yu Zhu; Fan, Yu Zhu; Zhou, Jiao; Zhang, Xing Yue; Li, Nian Bing; Luo, Hong Qun
Abstract : A dual-ligand lanthanide coordination polymer is designed for ratiometric fluorescence and visual detection of Pi. Abstract : Developing novel luminescent materials for sensitive and rapid detection of phosphate (Pi) is vital in clinical diagnoses and water-quality monitoring. Herein, a lanthanide coordination polymer (NH2 -BDC–TbGMP CPs)-based ratiometric fluorescent probe is designed for quick and visual detection of Pi. The NH2 -BDC–TbGMP CPs are prepared via the self-assembly of 2-aminoterephthalic acid (NH2 -BDC) and guanine monophosphate (GMP) with terbium ions (Tb 3+ ). After the formation of NH2 -BDC–TbGMP CPs, the inherent fluorescence of NH2 -BDC is quenched via static quenching, while the nonluminous Tb 3+ can emit strong green fluorescence due to the antenna effect between Tb 3+ and GMP. In the presence of Pi, Pi can competitively combine with Tb 3+ to interrupt the interaction of the NH2 -BDC–TbGMP CP system, further causing a decrease in the fluorescence of Tb 3+ and an increase in the emission of NH2 -BDC. Accordingly, the ratiometric fluorescence sensing of Pi can be achieved by continuously recording the variations of two fluorescence signals. The corresponding fluorescence intensity ratio of Tb 3+ to NH2 -BDC ( F 547 / F 425 ) is linearly correlated with the Pi concentration in the range of 0.5 to 100 μM, with a detection limit of 0.13 μM. This strategy offers a simple, rapid, and sensitive method for the ratiometric fluorescence and visual sensing of Pi, which shows great application potential for water-quality monitoring.